Sur la géométrie des ensembles de nœuds pour l’interpolation de Lagrange en plusieurs variables - Bertrand, François (Comptes Rendus. Mathématique)
Given a valid set $X$ of interpolation points for Lagrange interpolation of degree $d$ in $n$ variables we study how many subsets of $X$ can be chosen in order to obtain a valid set of interpolation points of degree $d-1$. This leads to an estimate of the number of Newton structures for $X$ which, in turn, gives the number of different unisolvent sets that can be obtainend by the process of interwinning which is recalled in the text.